2015
DOI: 10.1111/apha.12460
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of microRNA‐375 expression alters voltage‐gated Na+ channel properties and exocytosis in insulin‐secreting cells

Abstract: AimMiR-375 has been implicated in insulin secretion and exocytosis through incompletely understood mechanisms. Here we aimed to investigate the role of miR-375 in the regulation of voltage-gated Na+ channel properties and glucose-stimulated insulin secretion in insulin-secreting cells.MethodsMiR-375 was overexpressed using double-stranded mature miR-375 in INS-1 832/13 cells (OE375) or downregulated using locked nucleic acid (LNA)-based anti-miR against miR-375 (LNA375). Insulin secretion was determined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 28 publications
2
47
0
Order By: Relevance
“…The authors observed that the overexpression of microRNA-375 in INS-1 832/13 cells led to a decrease in the protein levels of Scn3a and Scn3b. Nevertheless, the relevance of this regulation is not completely understood in a more physiologic context, because glucose-induced insulin secretion was not affected by knocking down microRNA-375 (Salunkhe et al, 2015).…”
Section: Nav Channels Modulation By Endogenous Moleculesmentioning
confidence: 99%
“…The authors observed that the overexpression of microRNA-375 in INS-1 832/13 cells led to a decrease in the protein levels of Scn3a and Scn3b. Nevertheless, the relevance of this regulation is not completely understood in a more physiologic context, because glucose-induced insulin secretion was not affected by knocking down microRNA-375 (Salunkhe et al, 2015).…”
Section: Nav Channels Modulation By Endogenous Moleculesmentioning
confidence: 99%
“…Cells were maintained in RPMI 1640 medium containing 11.1 mM glucose (HyClone, UT, USA) as previously described (Salunkhe et al, 2015). Both cell lines were incubated in a humidified atmosphere with 5% CO 2 at 37 °C for 48 h. All experiments were performed within culture passages in which the cell lines respond robustly to glucose-stimulated insulin secretion assay.…”
Section: Methodsmentioning
confidence: 99%
“…42,45 Only a modest increment in the plasma concentration of these 2 miRNAs was noted, and the authors concluded that milk miRNAs serve just as a dietetic source. However, both miR-375 and miR-200c might also affect exosome formation via exocytotic/endocytotic pathways, 42,48,49 and the required amount of miRNAs for biological activity is also intensively debated. 32,50 It would be necessary to develop models that are more physiological, e.g.…”
Section: Dietary Milk-derived Mirnasmentioning
confidence: 99%